Pendidikan Islam Berdimensi Pluralisme - Sulpi Affandy (Permata : Jurnal Pendidikan Agama Islam, 2022)
This research discusses about the Islamic education dimension of pluralism. Background of the problem, due to the dimensions of Islamic education is not intact in the teach values the diversity of the learners, so that can lead to learners living in shades of intolerant when living side by side with a plural society-heterogeneous.This study uses a research approach literature review, literature research. The term literature research can refer to the writings or papers complete scientific or part of scientific works such as books, articles, journals, movies, news, writing a product and others, which support the source of research data about the Islamic education-based pluralism.While the source of the research data, the researcher makes use of two data sources, namely primary data source of literature on Islamic education-based pluralism, and the source of data secondary data literature has the power support to the research. While the technique of data analysis, researchers using the technique of content analysis, analysis of inductive, and analysis techniques descriptive and analytical.The results showed that Islamic education dimensionless pluralist is a model of education that are implemented to produce output that education has an awareness of high tolerance, and awareness of mutual respect ripe. Foundation education foundation consists of, the foundation of the theological, philosophical, juridical, psychological and sociological. While the hallmark of Islamic education dimensionless pluralist marked with the life principle of democracy, equality and justice, oriented on humanity, togetherness, and peace, as well as develop an attitude admit, accept, and appreciate cultural diversity.Keyword: Education; Islamic Education; Pluralism. Abstrak Penelitian ini membahas tentang pendidikan Islam berdimensi pluralisme. Latar belakang masalahnya, disebabkan karena dimensi pendidikan Islam dirasa tidak utuh dalam mengajarkan nilai-nilai keberagaman kepada peserta didik, sehingga dapat menyebabkan peserta didik hidup dalam nuansa intoleran ketika hidup berdampingan dengan masyarakat yang plural-heterogen.Penelitian ini menggunakan pendekatan penelitian literature review, literature research. Istilah literature research dapat merujuk pada tulisan-tulisan atau paper-paper ilmiah lengkap atau bagian dari karya ilmiah seperti buku, artikel, jurnal, film, berita, tulisan suatu produk dan lain-lain, yang mendukung sumber data penelitian tentang pendidikan Islam berbasis pluralisme.Sementara sumber data penelitian, peneliti memanfaatkan dua sumber data, yakni sumber data primer kepustakaan mengenai pendidikan Islam berbasis pluralisme, dan sumber data sekunder yang data-data kepustakaannya memiliki daya penunjang terhadap penelitian. Sedangkan teknik analisis data, peneliti menggunakan teknik analisis konten, analisis induktif, dan teknik analisis deskriptif analitik.Hasil penelitian menunjukan bahwa pendidikan Islam berdimensi pluralis adalah sebuah model pendidikan yang dilaksanakan untuk menghasilkan output pendidikan yang memiliki kesadaran toleransi tinggi, dan kesadaran saling menghargai yang matang. Landasan pendidikan pluralis terdiri dari, landasan teologis, filosofis, yuridis, psikologis dan sosiologis. Sementara ciri khas pendidikan Islam berdimensi pluralis ditandai dengan prinsip hidup berdemokrasi, kesetaraan dan keadilan, berorientasi pada kemanusiaan, kebersamaan, dan kedamaian, serta mengembangkan sikap mengakui, menerima, dan menghargai keragaman budaya.Kata Kunci: Pendidikan; Pendidikan Islam; Pluralisme.